Profile of teaching profession - Spajić-Vrkaš, Vedrana (Array, 2004)
The work describes the challenges, solutions and obstacles met by European teachers in general and SEE teachers in particular in the face of complex social, economic, political, cultural and technological changes. The author argues that the effectiveness of education systems depends on enhancing the quality of teaching, which again depends on how we intervene in the system of teacher training, employment, salaries, working conditions, etc., and, consequently, calls for a holistic and inclusive education reforms. Five points are discussed in particular: the European priorities in regard to teacher training ; the limits to improving teacher profession in SEE ; the ongoing changes in Europe and the state-of-the-art in SEE ; the teachers'implicit values as a forgoten dimension in reform discussions, and suggestions for improvement, including the issues such as the changing of attitudes towards education, promoting data compillation and analysis, advancing teacher-training policy and implementation measures, as well as teacher working conditions and promoting teachers as leaders of education reform.